2015
DOI: 10.3109/08039488.2015.1074283
|View full text |Cite
|
Sign up to set email alerts
|

Is there an interrelationship between the effects of antipsychotics on psychopathology and on metabolism?

Abstract: Weight loss was not associated with a worsening of psychosis. The interrelationship between the antipsychotic-induced weigh gain and improved schizophrenia psychopathology observed in earlier studies appears to be indirect. Orlistat treatment in our study did not worsen psychopathology in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The supplementary search through the reference sections of the identified studies resulted in the inclusion of two additional articles. Thus, a total of 14 studies that reported on the relationship between serum lipids and symptoms of schizophrenia over the course of antipsychotic treatment were retained [8,9,[11][12][13][14][15][16][17][18][19][20][21]. One study was a case report, two were randomized controlled trials, and 11 were observational studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The supplementary search through the reference sections of the identified studies resulted in the inclusion of two additional articles. Thus, a total of 14 studies that reported on the relationship between serum lipids and symptoms of schizophrenia over the course of antipsychotic treatment were retained [8,9,[11][12][13][14][15][16][17][18][19][20][21]. One study was a case report, two were randomized controlled trials, and 11 were observational studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies that reported the association between changes in serum lipids and changes in symptoms (n = 12) [8, 9, 11-16, 18, 19, 21, 22], 9 studies found inverse associations [8, 9, 11-13, 15, 16, 18, 21], whereas three studies did not find significant associations [14,19,22]. The remaining two studies found significant associations but carried out the analysis without using repeated measures of the dependent and independent variables.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is a possibility that other factors, not identified in our research, could modulate the metabolic status of our patients. The patient's individual properties could cause particular metabolic patterns [30], as described in a case of olanzapine-induced dyslipidemia and hyperglycemia without an increase in weigh [31].…”
Section: Discussionmentioning
confidence: 99%